'Occupied territory is occupied territory': James Baldwin, Palestine and the possibilities of transnational solidarity. Issue 9 (1st September 2016) - Seidel, Timothy
Abstract: In his 1966 essay 'A Report from Occupied Territory', James Baldwin wrote that 'occupied territory is occupied territory, even though it be found in that New World which the Europeans conquered'. Though written 50 years ago, Baldwin's observations continue to resonate, indicating historical trends across geographical experiences affected by the legacy of colonialism. A growing theme in development and peace building studies relates to a kind of boundary crossing that sees academics and activists drawing linkages across spatial and temporal divides. The situation in Palestine–Israel has taken an increasingly central role in mobilising transnational solidarities that cross such boundaries. By examining James Baldwin's analysis of Harlem's 'occupation' – as well as drawing from a range of voices such as Achille Mbembe, Frantz Fanon, Edward Said, Toni Morrison and Laleh Khalili – this paper will explore the shared experiences of racism, colonialism, military occupation and dispossession that separate and divide, and the possibilities for transnational solidarities that defy those separations.